Mechanisms of ferroptosis in chronic kidney disease - Zhuo, Wen-Qing; Wen, Yi; Luo, Hui-Jun; Luo, Zhu-Lin; Wang, Li (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a newly identified form of regulated cell death characterized by iron accumulation and lipid peroxidation. Ferroptosis plays an essential role in the pathology of numerous diseases and has emerged as a key area of focus in studies of chronic kidney disease (CKD). CKD is a major public health problem with high incidence and mortality that is characterized by a gradual loss of kidney function over time. The severity and complexity of CKD combined with the limited knowledge of its underlying molecular mechanism(s) have led to increased interest in this disease area. Here, we summarize recent advances in our understanding of the regulatory mechanism(s) of ferroptosis and highlight recent studies describing its role in the pathogenesis and progression of CKD. We further discuss the potential therapeutic benefits of targeting ferroptosis for the treatment of CKD and the major hurdles to overcome for the translation of in vitro studies into the clinic.